(untitled) (Medical Forum Monthly, 2024)
Objective: Left renal vein is unique in its tributaries, course and drainage area. The complex embryological developmental pathway and genetic factors may render variability to anatomy of left renal vein. Most of the previous studies on left renal vein have been conducted in non Asian countries with very little contribution from Asia. So this study was designed to study normal and variable anatomical patterns of left renal vein in Pakistani people. Study Design: Observational / cross sectional study. Place and Duration of Study: This study was conducted in Forensic & Anatomy departments of King Edward, Fatima Jinnah, Allama Iqbal Medical College and Postgraduate Med. Institute Lahore from Feb. 2008 to Jan. 2009. Materials and Methods: There were fifty male cadavers. Cadavers dissection was carried out. Left renal vein along with kidney was exposed. A small cut was given in inferior vena cava and a mixture of gelatin with Indian ink was injected. Left renal vein and its variants were outlined and studied. Results: Normal preaortic vein was found in 84% of cases. Other patterns of left renal vein observed in this study were circumaortic (2%), retroaortic (2%), double (2%) and proximally double renal vein (10% of cases). Conclusion: This first of its kind study from Pakistan which shows renal vein varints are not uncommon and have impotant implications from surgical and radiological perspective. It provides an anatomical reference for future research in the fields of surgery and radiology.